2022
DOI: 10.1021/acs.est.1c04795
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl and Polyfluoroalkyl Substances in Groundwater Used as a Source of Drinking Water in the Eastern United States

Abstract: In 2019, 254 samples were collected from five aquifer systems to evaluate perfluoroalkyl and polyfluoroalkyl substance (PFAS) occurrence in groundwater used as a source of drinking water in the eastern United States. The samples were analyzed for 24 PFAS, major ions, nutrients, trace elements, dissolved organic carbon (DOC), volatile organic compounds (VOCs), pharmaceuticals, and tritium. Fourteen of the 24 PFAS were detected in groundwater, with 60 and 20% of public-supply and domestic wells, respectively, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 53 publications
6
46
0
Order By: Relevance
“…Their study reported a random forest classifier that successfully discerned total PFAS concentrations over 70 ppt with an AUC of 0.90 (George and Dixit, 2021). In another recent study, McMahon et al trained boosted regression trees for predicting whether one or more of 24 PFAS was above the detection limit in 254 groundwater samples, which was the case for 54% of the samples; the AUC for the complete data set was 0.97 but decreased to 0.90 in cross-validation (McMahon et al, 2022). The robust performance of the classification models in our study might result from the much larger sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study reported a random forest classifier that successfully discerned total PFAS concentrations over 70 ppt with an AUC of 0.90 (George and Dixit, 2021). In another recent study, McMahon et al trained boosted regression trees for predicting whether one or more of 24 PFAS was above the detection limit in 254 groundwater samples, which was the case for 54% of the samples; the AUC for the complete data set was 0.97 but decreased to 0.90 in cross-validation (McMahon et al, 2022). The robust performance of the classification models in our study might result from the much larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the rest of the study area is more rural, especially in Washington County. McMahon et al investigated the relationship between land use and PFAS occurrence in groundwater and reported that sampling sites having PFAS detections tended to have a significantly larger percentage of urban land within 500 m than sites with no detections (McMahon et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…31,74,75 For example, PFASs were detected in 60% of public-supply wells out of 254 sampled wells in the Eastern United States. 76 Where do these PFASs come from, and how does this relate to soil PFASs pollution? It is known that most traditional persistent organic pollutants (POPs) have strong lipophilic and hydrophobic properties.…”
Section: Environmental Fate and Potential Hazards Of Soil Pfassmentioning
confidence: 99%
“…Evidence has shown that many cationic and zwitterionic PFAS are released into the environment, whereas traditional treatment ignores most of them [9] . Considering the co‐existence of various PFAS in water, a high‐performance adsorbent with broad‐spectrum affinity, i.e., one material can simultaneously adsorb PFAS with different properties, is highly demanded [10] …”
Section: Figurementioning
confidence: 99%
“…[9] Considering the co-existence of various PFAS in water, a high-performance adsorbent with broad-spectrum affinity, i.e., one material can simultaneously adsorb PFAS with different properties, is highly demanded. [10] Broad-spectrum affinity requires multitype interactions. Squaramides, as a family of conformationally rigid cyclobutene ring derivatives, are famous for their specific ability to act as dual hydrogen bond donors and acceptors.…”
mentioning
confidence: 99%